Economic Contribution in Education and Education in Economic Development of Sinjai Regency - Muh. Syawal Kurniawan; Andi Pangeran Manggasali; Diyah Fadillah; Nurwahida (www.amertainstitute.com, 2024)
Economic progress in Sinjai Regency is also influenced by the quality of education. Thus, education plays an important role in driving economic growth in the region. By increasing efficiency in the learning process, the younger generation who are studying can gain a deeper understanding of economics, so that they can make a significant contribution to economic progress in Sinjai Regency. Given the high economic needs that continue to grow, education plays an important role in producing quality human resources (HR). These HR will later influence economic growth in the future. Education is an effort to develop human resources that are able to produce HR to support development, while development itself is also a step to support educational progress through coaching, research, and provision of facilities. However, the success of an educational institution is more determined by factors other than economic aspects, namely the commitment, expertise, and abilities of its educators.